Incidencia del juego en la asignatura de educación física como método de enseñanza de valores en los niños y niñas de 8 a 10 años de la Unidad Educativa Blanca Villamarin Ortiz, del Cantón Montalvo, período 2022 - Renteria Potes, Giannella Andreina (2022)
The main objective of this case study was to analyze the Incidence of the game in the subject of physical education as a method of teaching values in children aged 8 to 10 years of the Blanca Villamarin Educational Unit, Montalvo Canton, Period 2022. Methodology: an investigation with a mixed approach (quali-quantitative), field-descriptive and with a non-experimental cross-sectional design was initiated. An intentional sample of 25 children (14 boys and 11 girls) was selected from two parallels (A and B). Instruments: A structured questionnaire of adapted physical education questions (children) and an interview (teachers and authorities) were applied. Results: The state of ten values that can be observed and analyzed from physical education classes (companionship, honesty, respect, discipline, solidarity, empathy, companionship, humility, tolerance, sincerity) was diagnosed. It was found that there are deficiencies in the values of respect, tolerance and discipline; because more than half of the sample do not maintain a pattern of discipline and order, they do not give their word or reason to their classmates or teachers, etc. Conclusion: It is necessary that the students, teachers and authorities of the Blanca Villamarin Educational Unit, of the Montalvo Canton, assign the necessary importance to the game within the physical education subject because it is the axis that articulates an adequate integral development in the child, promoting socio-affective, motor and cognitive spheres.